Temporary Employment, Demand Volatility and Unions: Firm-Level Evidence - Francesco Devicienti; Paolo Naticchioni; Andrea Ricci (Institute for the Study of Labor (IZA), 2015)
This paper investigates the effect of workplace unionization and product market volatility on firms' propensity to use temporary employment. Using Italian firm level data, we show that unionization and volatility have a positive impact on the share of temporary contracts. However, as volatility increases the union effect becomes negative, suggesting that in a highly volatile economic environment unions may be concerned about the weakening of their bargaining power associated with an extensive use of temporary workers. Furthermore, these effects are at work only for the use of non-training temporary contracts, while training temporary contracts are not affected by unions, volatility and their interplay. We argue that this occurs because non-training temporary contracts can be used by firms as a buffer stock to cope with uncertainty and by unions to protect insiders, while training temporary contracts are more likely to be used as a screening device for future permanent positions.
Keywords: J51; J23; J24; 330; product demand volatility; training; temporary workers; unions; firms